Understanding Misogynistic Hadith: Comparative Studies of Ibn Hajar Al-Asyqalani and Fatimma Mernissi - Muhammad Yazid Arrizqi; Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the understanding of misogynistic hadith, the comparative study of Ibn Hajar and Fatima Mernissi. This research is a qualitative type through literature study with analysis and comparison methods. The results and discussion of this study include the meaning of misogynistic hadith, understanding of misogynistic hadith according to Ibn Hajar and Fatima Mernissi, and comparative analysis of the understanding of Ibn Hajar and Fatima Mernissi. This research concludes that misogynist hadiths need to be reexamined and cannot be understood textually. This study recommends especially for Islamic religious extension workers to be able to provide understanding to Muslim audiences regarding the understanding of misogynistic hadith.